The Character of Semar in Wayang: A Synthesis of Javanese Cultural Philosophy and Islamic Principles - Ulfah, Yetty Faridatul; Abbas, Ngatmin; Setiawan, Andi; Ahmad Yasin, Zulfi; Sholehuddin, Yusron (Universitas Islam Negeri Sumatera Utara, 2025)
The character of Semar in Javanese puppetry is a unique figure who bridges Javanese philosophy and Islamic teachings. This study explores the synthesis between the two traditions through an analysis of Semar's characteristics and teachings. This study aims to (1) analyze how the character of Semar represents the synthesis between Javanese cultural philosophy and Islamic principles, (2) examine its implications for understanding cultural acculturation and (3) its relevance in the context of contemporary Indonesia. This study applied the library research method. Data sources included literature on puppetry, Javanese philosophy, and Islamic teachings. The analysis was conducted by using a hermeneutic, comparative, and semiotic approach. The study result reveal that (1) a significant correlation between the characteristics and teachings of Semar and the basic principles of Islam. Concepts such as